Developmental bias in the fossil record. Issue 1 (2nd September 2019) - Jackson, Illiam S. C.
Abstract: The role of developmental bias and plasticity in evolution is a central research interest in evolutionary biology. Studies of these concepts and related processes are usually conducted on extant systems and have seen limited investigation in the fossil record. Here, I identify plasticity‐led evolution (PLE) as a form of developmental bias accessible through scrutiny of paleontological material. I summarize the process of PLE and describe it in terms of the environmentally mediated accumulation and release of cryptic genetic variation. Given this structure, I then predict its manifestation in the fossil record, discuss its similarity to quantum evolution and punctuated equilibrium, and argue that these describe macroevolutionary patterns concordant with PLE. Finally, I suggest methods and directions towards providing evidence of PLE in the fossil record and conclude that such endeavors are likely to be highly rewarding. Abstract : Illustration of the process of plasticity‐led evolution in terms of phenotype, environmental stress and cryptic genetic variation (CGV). Ellipses represent populations in morphospace. The shading intensity of the ellipses gives their relative level of CGV. HIGHLIGHTS: Developmental bias may be manifest in the fossil record in patterns generated by the process of plasticity‐led evolution. Its signature is a coupling of increasing phenotypic variability and shifting phenotypic mean associated with environmental change. In a macroevolutionary context the predicted outcome of plasticity‐led evolution resembles quantum evolution and punctuated equilibrium.